A constituição da docência no curso de formação em Educação Física : os modos de ser, saber e poder ser professor - Souza, Adrielle Lopes de (2015)
The constitution of teacher identity is a process that involves a whole life story. In the case of higher education teachers, it is observed that the process of becoming a university professor implies singularities and subjectivities, which sometimes turn away, now approaching, according to the formation of origin of these teachers. Thus, this study aimed to understand how the teachers who work in the courses of Physical Education, the Center for Physical Education and Sports of the Federal University of Espirito Santo (CEFD / UFES), recall their teaching establishment and how to understand their process to become a professor of higher education. To this end, the narratives of the life histories of the participating teachers were used. The sample that participated in this research consisted of five teachers, entering the last five years of the effective framework of CEFD / UFES. To analyze the narratives of employee’s teachers, it was revealed that teachers address the conceptions of teaching so that acknowledge the different dynamics and joints to reflect on their own professional practices. Through narratives, teachers are faced with a multitude of elements that were perceived from their life stories. Emerged three areas of discussion: the ways of "being a teacher"; ways of "knowing-be teacher" and ways to "be able to be a teacher." It is concluded that the three axes of analysis are connected and make up the actual construction of teacher identity. Regarding ways of "being a teacher" refers to becoming a teacher, including teaching as a lived career, a career that cannot be learned from a unique experience only or through specific training, but as a process under construction, based on diverse experiences and social relationships built up over the life of the university teacher. On ways of "how to be a teacher" are related to the aspects that make up the university teaching, taking into account the pedagogical knowledge, involving the training and the professional experience of university teachers. In turn, the modes of "power to be a teacher" are the challenges of the profession, the difficulties encountered with the intensification of teachers' work, and the lack of time for activities in their spare time. So it is hoped that this research will enable autoaffirmatives times, causing reflections on the life story of academics, contributing to the understanding of his teaching establishment.